DETERMINATION OF ECONOMIC INJURY LEVEL (EIL) OF SUGARCANE PLASSEY BORER CHILO TUMIDICOSTALIS HAMPSON (LEPIDOPTERA: PYRALIDAE) - R. K. NATH; D. K. SAIKIA (The Bioscan, 2020)
Field experiment was conducted at Krishi Vigyan Kendra, Assam Agricultural University, Tinsukia during 2016 to determine the economic injury level of sugarcane plassey borer Chilo tumidicostalis Hampson (Lepidoptera: Pyralidae). The EIL was determined by using the method given by Stone and Pedigo (1972). From the investigation, it was observed that the per cent loss in yield of sugarcane due to secondary infestation by the plassey borer varied from 2.84 to 11.15 per cent.The intensity of borer attack in terms of number of internodes damaged due to secondary infestation varied from 15.38 to 58.33 per cent. The economic injury level of sugarcane plassey borer was determined in case of per cent internode infestation and was 17.6 per cent. However, the economic injury level is the dynamic parameter with the variety, the management practices in a particular area, the stage of the crop at infestation, the market price of the produce and the cost of insect control.